Health status of bycaught Common Eiders (Somateria mollissima) from the Western Baltic Sea - Schick, Luca A.; Wohlsein, Peter; Rautenschlein, Silke; Jung, Arne; Boyi, Joy Ometere; Glemarec, Gildas; Kroner, Anne-Mette; Barth, Stefanie A.; Siebert, Ursula (Animals, 2022)
The Common Eider (Somateria mollissima) inhabits the entire northern hemisphere. In northern Europe, the flyway population reaches from the southern Wadden Sea to the northern Baltic coast. The European population is classified as endangered due to declines in Common Eider numbers across Europe since 1990. In this study, we assessed 121 carcasses of Common Eiders, captured incidentally in gillnets in the Western Baltic between 2017 and 2019. The most common findings were parasitic infections of the intestine by acanthocephalans in 95 animals, which correlated with enteritis in 50% of the cases. Parasites were identified as Profilicollis botulus in 25 selected animals. Additionally, oesophageal pustules, erosions, and ulcerations, presumably of traumatic origin, were frequently observed. Nephritis and hepatitis were frequent, but could not be attributed to specific causes. Lung oedema, fractures and subcutaneous haemorrhages likely resulted from entangling and drowning. Two Common Eiders had mycobacterial infections and in one of these, Mycobacterium avium subspecies (ssp.) avium was identified. This study gives an overview of morphological changes and infectious diseases from one location of the European flyway population. It contributes to future health studies on Common Eiders in the Baltic and Wadden Seas by providing baseline information to compare with other areas or circumstances.